Constructive Field Theory in Zero Dimension - V. Rivasseau (Advances in Mathematical Physics)
Constructive field theory can be considered as a reorganization of perturbation theory in a convergent way. In this pedagogical note we propose to wander through five different methods to compute the number of connected graphs of the zero-dimensional 𝜙4 field theory, in increasing order of sophistication and power.